Eksistensi Lembaga Adat Dalam Penyelesaian Sengketa Pertanahan - Mahu, Muhammad Ridwan; Nirahua, Salmon Eliazer Marthen; Salmon, Hendrik (Pusat Kajian Pesisir dan Masyarakat Hukum Adat Fakultas Hukum Universitas Pattimura, 2023)
In customary law communities, disputes have long been resolved by deliberation and consensus through customary institutions known as customary courts. Usually, those who act as judges in these institutions are traditional leaders (customary heads) and religious leaders. The purpose of this study is to determine and analyze the position of customary institutions in resolving land disputes, as well as whether the decisions of customary institutions have binding legal force. This research is a normative juridical research, using a descriptive analytical research type using primary, secondary and tertiary legal sources. The approach used is a statutory approach (Statute Approach), a conceptual approach (conceptual approach) and a case approach (Case Approach). The technique of collecting legal materials uses a literature study which is then analyzed qualitatively in order to answer the problems studied. The position of customary institutions in land disputes as Customary Judicial Institutions used to resolve conflicts that generally occur in customary law communities is by way of dispute resolution outside the court according to the customary law system based on peace and harmony in people's lives. The decisions of the Customary Courts have binding force on the disputing parties, although in the hierarchy of judicial power the decisions of customary judges are not explicitly recognized, but in practice the existence of customary judges decisions is still recognized as long as the customary law community is also recognized and implemented by the disputing parties so that every decisions issued by customary judges are binding on the customary law community concerned.